A Novel Hydrogen Sulfide Prodrug, SG1002, Promotes Hydrogen Sulfide and Nitric Oxide Bioavailability in Heart Failure Patients - David J. Polhemus; Zhen Li; Christopher B. Pattillo; Gabriel Gojon; Gabriel Gojon; Tony Giordano; Henry Krum (2015)
Summary Recent studies demonstrate robust molecular cross talk and signaling between hydrogen sulfide (H 2 S) and nitric oxide ( NO ). Heart failure ( HF ) patients are deficient in both H 2 S and NO , two molecules that are critical for cardiovascular homeostasis. A phase I clinical trial of a novel H 2 S prodrug ( SG 1002) was designed to assess safety and changes in H 2 S and NO bioavailability in healthy and HF subjects. Healthy subjects (n = 7) and heart failure patients (n = 8) received oral SG 1002 treatment in escalating dosages of 200, 400, and 800 mg twice daily for 7 days for each dose. Safety and tolerability were assessed by physical examination, vital signs, and ECG analysis. Plasma samples were collected during a 24‐h period each week for H 2 S and NO analysis. BNP and glutathione levels were analyzed as markers of cardiac health and redox status. Administration of SG 1002 resulted in increased H 2 S levels in healthy subjects. We also observed increased H 2 S levels in HF subjects following 400 mg SG 1002. Nitrite, a metabolite of NO , was increased in both healthy and HF patients receiving 400 mg and 800 mg SG 1002. HF subjects treated with SG 1002 displayed stable drug levels over the course of the trial. SG 1002 was safe and well tolerated at all doses in both healthy and HF subjects. These data suggest that SG 1002 increases blood H 2 S levels and circulating NO bioavailability. The finding that SG 1002 attenuates increases in BNP in HF patients suggests that this novel agent warrants further study in a larger clinical study.